1991
DOI: 10.1083/jcb.114.2.277
|View full text |Cite
|
Sign up to set email alerts
|

An increase or a decrease in myosin II phosphorylation inhibits macrophage motility.

Abstract: Abstract. Myosin II purified from mammalian nonmuscle cells is phosphorylated on the 20-kD light chain subunit (MLC2o) by the Cat+/calmodulin-dependent enzyme myosin light chain kinase (MLCK) . The importance of MLC2o phosphorylation in regulating cell motility was investigated by introducing either antibodies to MLCK (MK-Ab) or a Cat+/calmodulin-independent, constitutively active form of MLCK (MK -) into macrophages . The effects of these proteins on cell motility were then determined using a quantitative che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Phosphorylation of the 20-kDa MLC on the serine or threonine residue is an important determinant of contractile tension in both smooth muscle and nonmuscle cells (9,30,32). In this study, we demonstrated that EHEC infection induces time-dependent phosphorylation of MLC.…”
Section: Discussionmentioning
confidence: 59%
“…Phosphorylation of the 20-kDa MLC on the serine or threonine residue is an important determinant of contractile tension in both smooth muscle and nonmuscle cells (9,30,32). In this study, we demonstrated that EHEC infection induces time-dependent phosphorylation of MLC.…”
Section: Discussionmentioning
confidence: 59%
“…In our previous work on vesicle mobility, we (Seabrooke et al 2010) likewise found similar phenotypic effects when NMMII was up-or downregulated. Additionally, a study of macrophage motility reported that inhibition or enhancement of Myosin II phosphorylation both had the same effect on cell migration (Wilson et al 1991). Furthermore, phosphorylation of the regulatory light chain of NMMII is crucial for cytokinesis (Matsumura 2005), but overexpression of myosin II in fission yeast inhibits cytokinesis (May et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In monocytes/ macrophages, MLCK is implicated in several activities important in atherosclerosis. Thus, MLCK is important for macrophage motility 19 and regulates neutrophil migration across the endothelium. 20 MLCK activation was recently proven to be critical in cytoskeletal changes resulting in pseudopod formation during phagocytosis.…”
mentioning
confidence: 99%